2019
DOI: 10.1177/0886260519832905
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospital Admissions for Intimate Partner Violence in Australian Mothers With Children Born From 1990 to 2009

Abstract: This study aims to determine the prevalence, and trends over time, of Western Australian (WA) mothers who were victims of intimate partner violence (IPV) requiring hospital admission. The study investigated the prevalence of all mothers and the specific prevalence of Aboriginal and non-Aboriginal mothers. A population-based cohort study using de-identified linked health data of mothers of children born from 1990 to 2009 in WA was carried out. The prevalence of hospitalizations for IPV in mothers of children bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 35 publications
4
26
0
1
Order By: Relevance
“…The disclosure of IPV during the screening assessment was significantly associated with a diagnosis of a perinatal mental health disorder, this is consistent with the known adverse impacts of IPV on mental health [53,54]. We note that Aboriginal women are disproportionately impacted by IPV [55] and often hesitant to discuss IPV with health professionals due to concerns that information may be used to justify the removal of their children by statutory services [56]. Approaches that are culturally safe and strengths based are more likely to be acceptable for Aboriginal women and provide a starting place for support [53,56] and the KMMS may assist with this.…”
Section: Discussionsupporting
confidence: 79%
“…The disclosure of IPV during the screening assessment was significantly associated with a diagnosis of a perinatal mental health disorder, this is consistent with the known adverse impacts of IPV on mental health [53,54]. We note that Aboriginal women are disproportionately impacted by IPV [55] and often hesitant to discuss IPV with health professionals due to concerns that information may be used to justify the removal of their children by statutory services [56]. Approaches that are culturally safe and strengths based are more likely to be acceptable for Aboriginal women and provide a starting place for support [53,56] and the KMMS may assist with this.…”
Section: Discussionsupporting
confidence: 79%
“…2 3 Surveys conducted for other purposes (eg, health surveys) which include a dedicated module on family violence provide some information, but can also be problematic, as space limitations for specific modules means that they might not be able to include questions that canvas the full range of violent experiences. 5 The emerging consensus is that 'population-based stand-alone surveys are the instruments of choice' for collecting statistics on violence against women. 6 To date, specific violence against women surveys have been carried out in several high-income countries (eg, USA, 7 Canada, 8 Australia, 9 European Union, 10 Finland, 11 12 Spain, 13 New Zealand 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seventy percent of this cost is attributed to injuries caused by spouse/domestic partner or a family member. Furthermore, a study of hospital admissions following IPV in women in Western Australia found an overall increase in the number of IPV related admissions between 1990 and 2009 (Orr et al, 2019).…”
Section: Introductionmentioning
confidence: 99%